TELAAH HUKUM ISLAM MENGENAI UTANG PIUTANG SISTEM IJO (NGIJO) - Nur Afifatun Nadhiroh (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
Ijo system (Ngijo) are farmers borrow money to collectors, the money will be paid with rice, with a standard or kwintalan size at harvest time. In practice the agreement Ngijo Village Sebayi the District Gemarang Madiun County only carried out by the farmer with the collectors only verbally and in the absence of witnesses, so that the interference village head or an authorized officer is not required, so Ngijo done only with mutual trust alone or by customs local. If farmers do defaults by not paying debts when the farmer has a crop, then the collectors do not hesitate to ask for money back and cancel the agreement, and if farmers are not able to provide rice at maturity (harvesting), then the farmer will give paddy season The next harvest rice by adding 5% for repayment. From the above results, it can be concluded that the first, the system of Ijo (Ngijo) conducted in the absence of witnesses caused the contract not perfect, which means the contract made invalid. Secondly, the system of Ijo (Ngijo) not including contract qard (debts) because of the mismatch between the principal amount of debt by the amount of the repayment, as well as the additional 5% of rice when farmers could not pay off the debt at maturity (harvest), which aims to take more profits for the muqrid, then the accounts payable system of Ijo (Ngijo) is not in accordance with Islamic law, because it belongs to the category of riba nasi'ah which is haram.